Discrete inverse and state estimation problems : with geophysical fluid applications - Wunsch, Carl (Cambridge University Press, 2006)
Addressing the problems of making inferences from noisy observations and imperfect theories, this book introduces many inference tools and practical applications. Starting with fundamental algebraic and statistical ideas, it is ideal for graduate students and researchers in oceanography, climate science, and geophysical fluid dynamics.